2017
DOI: 10.1039/c7ra08257f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of carbon nanofibers by thermal conversion of the molecular precursor 5,6;11,12-di-o-phenylenetetracene and its application in a chemiresistive gas sensor

Abstract: Carbon nanofibers with an amorphous solid structure have been synthesized by thermal conversion of the polycyclic aromatic hydrocarbon 5,6;11,12-di-o-phenylenetetracene (DOPT) at 1000 C on various substrates. Rapid annealing of DOPT on copper foil, SiO 2 /Si wafer and a SiO 2 /Si wafer coated with a 20 nm thick layer of Pt/Pd resulted in growth of carbon nanofibers. The most effective synthesis of these fibers was realized on the latter substrate. The Pt/Pd layer segregates by dewetting under thermal treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…There are also other strategies to synthesize CNFs, such as the thermal conversion of hydrocarbons on various substrates [77,78], electrospinning with coaxial nozzles [79], and template synthesis in porous substrate [80][81][82]. These methods are often used to prepare CNFs with special structures and assembly forms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are also other strategies to synthesize CNFs, such as the thermal conversion of hydrocarbons on various substrates [77,78], electrospinning with coaxial nozzles [79], and template synthesis in porous substrate [80][81][82]. These methods are often used to prepare CNFs with special structures and assembly forms.…”
mentioning
confidence: 99%
“…These methods are often used to prepare CNFs with special structures and assembly forms. For example, Krauß et al [77] reported amorphous CNFs by thermal transformation of polycyclic aromatic hydrocarbon 5,6;11,12-di-o-phenylenetetracene, and Wang et al [82] synthesized CNFs containing linear mesocage arrays where the cages were formed via the evaporation of solvent.…”
mentioning
confidence: 99%